The precious gift : a Navaho creation myth - Jackson, Ellen B., 1943-; Hubbard, Woodleigh (New York : Simon & Schuster Books for Young Readers, 1996)
A retelling of part of a Navajo creation and evolution myth in which of all the animals the lowly snail alone is responsible for bringing pure water to the new land.
Elem. School Library Collection.
School Library Journal.
Book Links (A.L.A.).
4.8
K-3
Keywords: Navajo Indians -- Folklore; Tales -- Southwest, New; Snails -- Folklore; Snails -- Folklore; Navajo Indians -- Folklore; Indigenous people of North America -- Folklore; Folklore -- Southwest, New; Snails -- Folklore; Navajo Indians -- Folklore; Native Americans -- Southwestern States -- Folklore; Folklore -- Southwestern states; Snails -- Folklore; Navajo Indians -- Folklore; Indigenous people of North America -- Folklore; Folklore -- Southwest, New